Influence evaluation of PM₁₀ produced by the burning of biomass in Peru on AOD, using the WRF-Chem - Navarro Barboza, Héctor (2020)
This study assesses the influence of PM₁₀ on the optical thickness of aerosols in the central Andes of Peru, in addition to analyzing and establishing their circulation patterns from July to October 2017. This particular period is considered herein because the largest biomass burning events are usually recorded during these months. The regional meteorological-chemistry transport model WRF-Chem (version 3.7) was used with the Fire Inventory from NCAR (FINN) fire emissions dataset and aerosol optical depth (AOD) data from the Aerosol Robotic Network monitoring network (AERONET), which has a CIMEL sun photometer located at the Huancayo Observatory, the most important city in the central highlands of Peru. The simulation used a single domain with a grid size of 18 km and 32 vertical levels. Results showed an increase in PM₁₀ concentrations with an increase in the number of fire outbreaks and AOD during July, August, and September. In contrast, a slight decrease in PM₁₀ concentrations was recorded for October. Further, the meteorological conditions did not favor the occurrence of fire outbreaks in the Mantaro valley during the entire study period; however, an increase in rainfall reduced aerosol concentrations in October. In addition, although the vertical movements prevailing over the central Andes were ascending, they were descending along the Peruvian coast, thus favoring and hindering the dispersion of aerosols in the first and second cases, respectively. Finally, the authors assessed, analyzed, and confirmed the influence of biomass burning on AOD in the studied region.